Cover Picture: Establishing the Stability and Reversibility of Protein Pyrophosphorylation with Synthetic Peptides (ChemBioChem 3/2015). Issue 3 (9th February 2015) - Yates, Lisa M.; Fiedler, Dorothea
<x xml:space="preserve">Abstract</x> The cover picture shows the enzyme‐mediated reversal of peptide pyrophosphorylation, a poorly characterized modification to date. Previous in vitro studies on peptide and protein substrates revealed that this modification was installed nonenzymatically by the inositol pyrophosphates, a central group of cellular messengers, after a priming phosphorylation event by casein kinase 2. In their work (see p. 415 ff.), D. Fiedler and L. M. Yates used a set of synthetic pyrophosphopeptides to demonstrate that the pyrophosphate functional group is generally chemically inert, but can be rapidly removed in vitro by alkaline phosphatases, as depicted in this scheme. Most significantly, this work has elucidated the enzyme‐dependent dephosphorylation of synthetic pyrophosphopeptides in eukaryotic cell lysates. The evidence for the reversibility of pyrophosphorylation and its intricate interplay with phosphorylation‐based networks highlight the potential impact of pyrophosphorylation in cellular signaling cascades.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>